Head-to-Head Comparison of the Hypoglycemic Efficacy and Safety Between Dipeptidyl Peptidase-4 Inhibitors and α-Glucosidase Inhibitors in Patients With Type 2 Diabetes Mellitus: A Meta-Analysis of Randomized Controlled Trials - Li, Zhaoliang; Zhao, Liang; Yu, Leilei; Yang, Jie (Frontiers in Pharmacology, 2019)
Background: The α-glucosidase inhibitors (AGIs) are commonly prescribed in Asian patients with type 2 diabetes mellitus (T2DM), but with a high incidence of gastrointestinal side effects. This study was aimed to compare the efficacy and safety of dipeptidyl peptidase-4 (DPP4) inhibitors and AGIs in T2DM patients in a meta-analysis. Methods: Randomized controlled trials were identified via systematic search of PubMed, Embase and Cochrane’s Library databases from inception to February, 2019. Meta-analyses were performed via a random or a fixed effect model according to the heterogeneity. Results: Eighteen studies with a total of 4,051 patients with T2DM were included. The DPP4 inhibitors were associated with lower reduction of HbA1c as compared with AGIs (weighed mean difference [WMD]: -0.37%, p < 0.001). Subgroup analyses indicated that the benefit of DPP4 inhibitors as compared with AGIs on HbA1c were independent of study design, scale, baseline HbA1c, with or without concurrent medications, or follow-up durations. Moreover, compared to AGIs, DPP4 inhibitors was associated with lower reductions of fasting blood glucose (WMD: -0.53 mmol/L, P < 0.001) and postprandial glucose at 2h (WMD: -0.60 mmol/L, P = 0.04), moderately increased body weight (WMD: 0.34 Kg, P = 0.02), decreased risk of gastrointestinal adverse events (risk ratio [RR]: 0.48, P < 0.001), but unaffected risk of symptomatic hypoglycemia (RR: 0.96, P = 0.90). Conclusions: The DPP4 inhibitors are superior to AGIs in T2DM patients for better glycemic control and lower risks of gastrointestinal side effects.